DISASTER RISK ANALYSIS AND UNDERSTANDING OF THE CEMARA KEMBAR BEACH COMMUNITY IN DISASTER MITIGATION EFFORTS - Susilawati, Susilawati; Ramadhani, Syaira Zhieka; Nasution, Sabrina Cahyati; Adriani, Novita Dwi; Daulay, Rangga Muriansyah; Naufal, Ahmad Fitra (LPPM Univ. Ibn Khaldun Bogor, 2025)
Cemara Kembar Beach in North Sumatra faces significant natural disaster risks, including abrasion, erosion, flash floods, and the impacts of climate change. The area is directly exposed to the sea, which increases vulnerability. Public understanding of disaster mitigation is about 70%, based on informant data. This study aims to analyze disaster risks and public awareness of mitigation efforts. Conducted using qualitative methods in Sei Nagalawan Village, the research involved interviews, observations, and documentation. The findings highlight that coastal areas are highly susceptible to disasters due to natural and human factors. Coastal erosion, caused by continuous sea waves, threatens settlements, while tropical storms and strong winds often bring flash floods. Rising sea levels due to climate change and human activities, such as mangrove logging, exacerbate the region's vulnerability. Public awareness of environmental protection is still low, further increasing flood risks during heavy rainfall. The study concludes that the community faces significant risks, including abrasion and flash floods, worsened by environmental damage and climate change, particularly affecting local rice fields. Public awareness and disaster mitigation measures are insufficient, contributing to the region’s vulnerability. Strategies such as mangrove planting, environmental education, waste management, and early warning systems have been identified as vital for reducing disaster risks. Therefore, collaboration between the government and the community is essential to develop sustainable disaster risk mitigation programs and protect coastal ecosystems.